Outcomes of Head and Neck Microvascular Reconstruction in Hypercoagulable Patients - Nguyen, Trang T.; Egan, Katie G.; Crowe, Danielle L.; Nazir, Niaman; Przylecki, Wojciech H.; Andrews, Brian T. (Journal of Reconstructive Microsurgery, 2020)
Background Inherited coagulopathies and previous thrombotic events are often considered relative contraindications to microvascular reconstruction. We hypothesize that with planning, head and neck microvascular reconstruction can be successfully performed in hypercoagulable individuals.Methods A retrospective review was conducted of subjects with coagulopathies or previous thrombotic events who underwent microvascular head and neck reconstruction. Outcomes studied were “flap-related complications” (arterial/venous compromise or flap loss) and “patient-related complications” (hematoma, deep venous thrombosis, pulmonary embolism, infection, stroke, or death).Results One hundred thirty-four microvascular flaps were performed in 117 subjects. Twenty-four subjects (20.5%) had a preoperative hypercoagulable condition and underwent 28 microvascular reconstructions. Twenty-three of 24 subjects had a previous thrombotic event, with five subjects identified with an inherited or acquired coagulopathy. All microvascular reconstructions were successful; however, complications occurred in 12 of 28 reconstructions (42.9%). Complications were “flap related” in four reconstructions (14.3%), “patient related” in nine reconstructions (32.1%), and both in one reconstruction (3.6%). Flap-related complications included small partial flap loss (n = 2), arterial compromise (n = 1), and venous compromise (n = 1), with all undergoing successful salvage. Patient-related complications included hematoma (n = 3), pulmonary embolism (n = 2), infection (n = 2), deep venous thrombosis (n = 1), and death (n = 1). Statistical analysis demonstrated that complications were more common in subjects with inferior vena cava filters (p = 0.06) and hematomas were associated with the use of therapeutic heparin infusion (p = 0.04).Conclusion Microvascular head and neck reconstruction can be successfully performed in hypercoagulable subjects. However, patient-related complications remain a concern in these subjects.
Keywords: thrombophilia; hypercoagulation; thrombosis; anticoagulation; microvascular reconstruction; microvascular flaps